Valorization of ferrochrome slag: towards increasing the beneficial utilisation of ferrochrome slag in South Africa - Sprinzl, Franz Robert Maria (Stellenbosch : Stellenbosch University, 2016)
Thesis (MEng)--Stellenbosch University, 2016.